The Incretins and Pancreatic β-Cells: Use of Glucagon-Like Peptide-1 and Glucose-Dependent Insulinotropic Polypeptide to Cure Type 2 Diabetes Mellitus - Kim, Mi-Hyun (Korean Diabetes Association, 2010)
Type 2 diabetes mellitus (T2DM) is increasing in prevalence worldwide. The complications associated with T2DM result in increased mortality and financial cost for those affected. T2DM has long been known to be associated with insulin resistance in peripheral tissues and a relative degree of insulin deficiency. However, the concept that insulin secretion and insulin sensitivity are not linked through a hyperbolic relationship in T2DM has continuously been demonstrated in many clinical trials. Thus, in order to prevent and treat T2DM, it is necessary to identify the substance(s) that will improve the function and survival of the pancreatic β-cells in both normal and pathologic conditions, so that production and secretion of insulin can be enhanced. Incretin hormones, such as glucagon-like peptide (GLP)-1 and glucose-dependent insulinotropic polypeptide (GIP), have been shown to lower the postprandial and fasting glucose and the glycated hemoglobin levels, suppress the elevated glucagon level, and stimulate glucose-dependent insulin synthesis and secretion. In this report, we will review the biological actions and mechanisms associated with the actions of incretin hormones, GLP-1 and GIP, on β-cell health and compare the differences between GLP-1 and GIP.